Evaluación de la presencia de Salmonella de Huevos Frescos, utilizando el medio Xilosa-Lisina-Tergitol 4 (XLT4) - Lévano Muñante, Gisella del Carmen (2001)
We evaluated the presence of Salmonella in 680 fresh hen eggs, coming from 4 farms from Lima and 4 ones from Chincha and from markets in Ate-Vitarte, Surco and Villa El Salvador. Eggshell and internal part were evaluated and the selectivity of Xylose-Lisine-Tergitol 4 agar medium (XLT4), checked up on the recuperation and isolation of species of Salmonella genus, with a statistical significance of p < 0,01 in comparison with Hecktoen agar medium.In the analysis of fresh eggs, Salmonella enterica serovar. Enteritidis was not found; however, we found Salmonella enterica serovar. Mbandaka.